Effects of compaction on embankment breach due to overtopping. Issue 2 (4th March 2017) - Asghari Tabrizi, Ali; Elalfy, Ezzat; Elkholy, Mohamed; Chaudhry, M. Hanif; Imran, Jasim
ABSTRACT: Despite many embankment failures worldwide, data on such failures are limited. An understanding of the embankment failure and the dominant parameters affecting the failure are crucial for predicting and modelling the breach process. Laboratory experiments are conducted on overtopping of embankments consisting of uniform homogenous sand and constructed with different levels of compaction. The temporal changes in the embankment surface profiles and the downstream discharge are measured. Two dimensionless equations are developed for the variation of crest height and embankment bottom length with time as a function of embankment-material dry density. A simple model assuming triangular shape is proposed for the development of breach shape for different compaction levels. Except during the initial stage of the failure, proposed model prediction and the observed data match satisfactorily. The proposed model for the crest height satisfactorily predicts the failure of a laboratory test and three dam failures in SC.